Characteristics of Men Who Seek Help From an Irish Domestic Abuse Helpline: The MENCALLHELP Study - Corbally, Melissa (My University, 2023)
Domestic violence and abuse (DVA) within relationships is a worldwide problem, which has detrimental direct and indirect consequences. Indeed, the negative health effects of DVA have been evidenced both nationally and internationally. It is also increasingly acknowledged that men experience DVA, and the gendered experience of DVA by those who identify as men has been explored in recent studies and reviews. However, there is still little known about how male victims of DVA utilize support services, particularly in countries like Ireland where masculinity stereotypes may be particularly powerful. In the present study, an exploratory statistical analysis of 10 months of retrospective contact data from a DVA support service based in Ireland was conducted, which included 3,181 contacts made by 1,093 individuals. Of this, 2,507 contacts were made by 715 men. Analyses provided evidence as to who contacts the service, what kinds of DVA are reported, how these behaviors are reported, and what kinds of outcomes result from this contact. Of the 715 men who made contact, they were most likely to be married, living apart from their partner, between the ages of 35 and 54, with an average of 2.1 children. All types of DVA were reported but psychological abuse was the most common, with 69.5% of the 2,507 contacts from male victims containing a report of psychological abuse. Contact was made by telephone in most cases (80%) and information was the most common outcome, being provided on 55.2% of contacts. Results provide important information about the utilization and characteristics of calls received by an Irish DVA support service, which will inform the enhancement of services provided to vulnerable men and their families.
PUBLISHED
Keywords: Domestic violence and abuse; Masculinity; Helpline; Men; Help-seeking; Inclusive Society; Domestic Violence; Helpline Evaluation; Gender; Justice and safeguarding